THE TRANSFORMATION OF THE BEUT DARÔH AND KENDURI KHATAM TRADITIONS IN THE URBAN COMMUNITY OF BANDA ACEH CITY - Muhajir Al-Fairusy; M. Ikhwan; Darlis Aziz; Muji Mulia (Akademika : Jurnal Pemikiran Islam, 2022)
This research examined the issue of religious traditions in Aceh from the perspective of understanding and interpreting the Quran. The research focuses on the beut darôh tradition, which culminates with the ceremony of kenduri khatam. In essence, this indigenous Acehnese ritual has been practiced for a long time in Acehnese culture and is exclusively celebrated during the month of Ramadan. The aim of beut darôh is to color the night during Ramadan after the tarawih prayer is done in every mosque and meunasah (Muslim house of worship), frequently in the midst of rural communities. This ritual culminated at the end of Ramadan with the commemoration of the kenduri khatam. This closing ritual encompasses the entire community. Aceh Besar and Banda Aceh were the primary locations to observe this practice evolving and changing. This research begins with the question, "Why are the beut darôh and kenduri khatam traditions able to develop in the middle of urban Acehnese society?" This study employed qualitative methodologies, incorporating grounded research. The findings of the study indicate that the beut darôh and kenduri khatam traditions are perceived as part of the Acehnese people's religious identity and culture. Beut darôh is not only a custom of reading the Quran together, but it is also an educational space for learning the Quran. Meanwhile, the people of Aceh view kenduri khatam as a sign of thankfulness as well as a social space including religious relationships and local traditions. Nonetheless, the beut darôh tradition, which was originally prevalent in Aceh's village communities, gradually expanded and persisted in Aceh's urban communities. In practice, however, there are some distinctions between the beut darôh tradition in rural and urban Acehnese societies.